Identifying the preparedness components in COVID-19: Systematic literature review - Pooneh Maziar; Ali Maher; Khalil Alimohammadzadeh; Mehrnoosh Jafari; Seyed Mojtaba Hosseini (Journal of Education and Health Promotion, 2022)
In 2019, the COVID-19 pandemic posed a major challenge to the world. Since the world is constantly exposed to communicable diseases, comprehensive preparedness of countries is required. Therefore, the present systematic review is aimed at identifying the preparedness components in COVID-19. In this systematic literature review, PubMed, Scopus, Web of Science, ProQuest, Science Direct, Iran Medex, Magiran, and Scientific Information Database were searched from 2019 to 2021 to identify preparedness components in COVID-19. Thematic content analysis method was employed for data analysis. Out of 11,126 journals retrieved from searches, 45 studies were included for data analysis. Based on the findings, the components of COVID-19 preparedness were identified and discussed in three categories: governance with three subcategories of characteristics, responsibilities, and rules and regulations; society with two subcategories of culture and resilience; and services with three subcategories of managed services, advanced technology, and prepared health services. Among these, the governance and its subcategories had the highest frequency in studies. Considering the need to prepare for the next pandemic, countries should create clear and coherent structures and responsibilities for crisis preparedness through legal mechanisms, strengthening the infrastructure of the health system, coordination between organizations through analysis and identification of stakeholders, culture building and attracting social participation, and service management for an effective response.